Preliminary experiments on potential use of blue monochromatic light for identification of cashew diseases (Research, Society and Development, 2024)
Cashew is a valuable crop for the world due to its nutritional, environmental, and economic qualities. However, it is challenged by abiotic and abiotic constraints such as diseases that cause significant yield losses. Various disease diagnostic and management strategies have been developed over time. But their adequacy is bound to a complex of advantages and disadvantages depending on host/pathogen relationships. Thus, the objective of this article was to describe a new approach that distinguishes cashew diseases by light at 405 nm.  Symptomatic tissues were, under aseptia, prepared for pathogen culturing and morpho cultural identification of the pathogen(s) associated. By inoculation and incubation of pathogens, disease symptoms were reproduced on cashew seedlings. Later, symptomatic tissues were then cut macerated in a 1/1(weight/water) extraction and allowed to precipitate at 4 oC. The supernatant was submitted to absorbance reading in a monochromatic beam of 405 nm. Sole extraction water and sole healthy tissue extracts were also considered. Three experiments with different treatments were conducted. Absorbance data were then processed statistically following a completely randomized design in which treatments consisted of individual plant/pathogen(s) extracts. The biotrophic pathogen O. anacardii resulted in the highest absorbance. However, it reduced in association with the necrotrophic pathogen Cryptosporipsis spp. No significant differences were discovered between the two necrotrophic pathogens Cryptosporipsis spp. and Septoria spp. The method demonstrated high potential for diagnosis of cashew diseases. Future research must focus on adjustable wavelength spectrophotometry and standardization. The method can be recommended for direct identification of field disease samples.